Rapid Assembly of Oxatricyclo[3.2.1.02,7]octanes - Xu, Lixia; Liu, Shuxuan; Han, Zhengyu; Huang, Hai; Sun, Jianwei (Synlett, 2025)
Cyclopropane-incorporated oxapolycyclic bridged molecules are often architecturally intriguing, synthetically useful, and biologically important. However, strategies for constructing such complex structures are relatively limited. This paper reviews representative methods that provide rapid access to a specific class of oxatricyclooctane frameworks containing cyclopropane, oxatricyclo[3.2.1.02,7]octane. A recent example of enantioselective construction of such a complex oxatricyclooctane structure is presented.1 Introduction2 Racemic Synthesis of Oxatricyclo[3.2.1.02,7]octanes3 Enantioselective Synthesis of Oxatricyclo[3.2.1.02,7]octanes4 Conclusion
Keywords: cyclopropane; strained rings; cascade reaction; bridged molecules; molecular complexity